Palladium-Gold Modified Ultramicro Interdigital Array Electrode Chip for Nitrate Detection in Neutral Water - Zhao, Shanshan (Micromachines (Basel), 2019)
An ultramicro interdigital array electrode modified by palladium-gold was developed for nitrate detection in neutral water. The ultramicro interdigital array electrode was fabricated based on silicon substrate by Micro Electro-Mechanical System (MEMS) technique. The nanostructured palladium-gold (Pd-AuNPs) composite sensing film was electrodeposited on the surface of a working electrode by electrochemical method. The synergistic effect of Pd-AuNPs composite was investigated and its enhancement of the catalytic activity and stability was revealed. The Pd-AuNPs modified electrode showed good linearity (R(2) = 0.99) from 1 mg/L to 15 mg/L (as N) for nitrate determination in a neutral water environment (pH = 7.2), with a sensitivity of 4.7 μA·mg(−1)·L. The results showed that the developed Pd-AuNPs-modified ultramicro interdigital array electrode chip can achieve sensitive and environmentally-friendly detection for nitrate in neutral water.